Dinamika dan Perkembangan Pengajian Rutin PRA Pabelan (Pimpinan Ranting Aisyiyah Pabelan) Meningkatkan Literasi Islam Masyarakat: Dynamics and Development of PRA Pabelan Routine Recitation (Aisyiyah Pabelan Branch Leader) Increasing Community Islamic Literacy - Tafana Dewi Kushandarini; Ludvi Nuraini; Diana Nur Umami; Maurisa Asry Ramadhani; Sefira Dona Puspita; Putri Maudy Puspitasari; Ahmad Nurrohim (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The community service program at PRA Pabelan aimed to enhance Islamic literacy by revitalizing routine religious lectures and implementing interactive learning at the Aisyiyah PAUD branch and Al Kausar Mosque TPQ. A situational analysis revealed passive participation and limited contextual materials, while partner challenges included one way teaching methods and lack of pedagogical innovation. The applied methodology combined participatory observation, direct instruction, and play based learning for early childhood education, alongside andragogical and visual auditory approaches in lectures and TPQ sessions. Results demonstrated increased active engagement, intrinsic motivation, basic motor and cognitive skills in children, and improved Iqra’ reading retention and short surah memorization. Sunday morning lectures fostered critical dialogue on contemporary Islamic issues with heightened attendee enthusiasm. Discussion confirms the efficacy of interactive methods in addressing partner challenges and strengthening socio religious networks. The program recommends ongoing facilitator training, development of thematic modules, and periodic evaluations to ensure sustainable educational and da’wah impacts.